ANO5 in membrane repair - Status: "It's complicated". (July 2021) - Gerke, Volker; Rescher, Ursula
Highlights: Anoctamin 5 (ANO5/TMEM16E) gene mutations are associated with skeletal muscle diseases ANO5 belongs to the anoctamin protein family that includes calcium-activated chloride channels ANO5-deficient cells are defective in Ca 2+ -dependent plasma membrane repair of muscle cells ANO5 could be a pharmaceutical target for treatment of ANO5-related muscle diseases Graphical abstract: Abstract: ANO5/TMEM16E gene mutations are associated with myopathies. Two recent publications in the Journal of Cell Biology now both confirm that ANO5 deficiency results in defective plasma membrane repair and Ca 2+ overload. But the big question is whether ANO5 acts at the plasma membrane or the endoplasmic reticulum.